NILAI SOSIAL PADA NOVEL PADANG BULAN KARYA ANDREA HIRATA (KAJIAN SOSIOLOGI SASTRA) - Afrianus Lapu; Indayani Indayani (Buana Bastra, 2018)
The selection of this novel as an object of research is based on a thought that the novel is lifted from human life to fight for its life, amidst the dynamics of social life, patience, laughter, devout worshipers, diligently working and learning, Shortcuts of love, caring. This study aims to describe the social values ​​contained in the novel "Padang Bulan" by Andrea Hirata. The theory used in this research is Sociology Literature. The subject of this research is the novel "Padang Bulan" by Andrea Hirata. The object of this study is the social value contained in the novel "Padang Bulan" by Andrea Hirata and as literary learning material. Data were analyzed using qualitative descriptive techniques. The results of this study are social values ​​in the novel "Padang Bulan" by Andrea Hirata. The variety of works consists of, patience, trust, worship, helpers, diligent work and study, love and care, all of these social values ​​are very appropriate for student character development.